The Authority of the Word and the Significance of Structure: A Study in the Narratives of Al Marwati - Narmeen Ghalib Ahmed; Azza Adnan Ahmed Ezzat (Zanco Journal of Human Sciences, 2026)
Al-Marwati presents highly distinctive texts that combine linguistic experimentation with psychological depth. He establishes a language of his own that challenges the familiar and creates its significations from the heart of strangeness. He uses his language in a deviant and displaced manner from its primary purpose. With a unique ability, using a single word from one or more linguistic roots, he generates structures in which the musicality of their words is consistent while their meanings are varied. The study is based on uncovering the unfamiliar strangeness in a selection of his titles and texts. It clarifies how) Al-Marwati (employed innovative and unconventional writing styles, with a focus on analyzing the deep meanings and significations that result from this stylistic uniqueness, which is out of the ordinary in narration. Furthermore, it demonstrates how his precise lexical choices contribute to the formation and construction of his own world, defining its unique atmospheres and features, in order to reveal the profound implications in his choices. The study sample consisted of some of his book titles and the peculiar words and structures within his narrative texts.